The Crosstalk between ROS and Autophagy in the Field of Transplantation Medicine. (19th December 2017) - Van Erp, Anne C.; Hoeksma, Dane; Rebolledo, Rolando A.; Ottens, Petra J.; Jochmans, Ina; Monbaliu, Diethard; Pirenne, Jacques; Leuvenink, Henri G. D.; Decuypere, Jean-Paul
Abstract : Many factors during the transplantation process influence posttransplant graft function and survival, including donor type and age, graft preservation methods (cold storage, machine perfusion), and ischemia-reperfusion injury. Successively, they will lead to cellular and molecular alterations that determine cell and ultimately organ fate. Oxidative stress and autophagy are implicated in posttransplant outcome since they are both affected by the stress responses triggered in each step (donor, preservation, and recipient) of the transplantation process. Furthermore, oxidative stress influences autophagy and vice versa. Interestingly, both processes have positive as well as negative effects on graft outcome, suggesting they are tightly linked during the transplantation process. In this review, we discuss the importance, regulation and crosstalk of oxidative signals, and autophagy in the field of transplantation medicine.